"This Goshen of the Alps": Il contributo dei viaggiatori britannici alla creazione dei "luoghi storici" delle Valli valdesi - Fratini, Marco (Rivista di storia della Chiesa in Italia, 2020)
At the beginning of the XVIII century the Waldensian Valleys of Piedmont became a destination for many British travelers (from England, Scotland and Ireland), both Anglican and Episcopalian. On the outskirts of the European Grand Tour and in a period of British missionary expansion, they looked for the rests of the pure Church of Christ, still faithful to the Apostolic principles, that has been survived against the corruption caused by Rationalism, Socinianism and Papism, in the edge of the Alps, between Protestant Europe and Italian Catholicism. Their experiences, strongly based on classical, biblical and romantic literary models, generated several travel accounts which contributed to create the “Waldensian world”, marked by Alpine landscape, characters and myths, capable of influencing readers in their homeland and even the Waldensians.